2006
DOI: 10.1614/wt-05-035r.1
|View full text |Cite
|
Sign up to set email alerts
|

Corn and Rice Response to Simulated Drift of Imazethapyr Plus Imazapyr

Abstract: Field research was conducted for 2 yr to evaluate response of corn and rice to simulated drift rates of a commercial premix of imazethapyr plus imazapyr [3:1 (w/w)]. Drift rates of the imazethapyr plus imazapyr premix represented 0.8, 1.6, 3.2, 6.3, and 12.5% of the usage rate of 63 g ai/ha (0.5, 1, 2, 4, and 7.9 g/ha, respectively). The imazethapyr plus imazapyr premix applied to six-leaf corn at 7.9 g/ha reduced height 11% compared with the nontreated control 7 days after treatment (DAT) but did not affect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
3
19
0
5
Order By: Relevance
“…Esses resultados podem ser explicados pelo fato de o cultivar IRGA 422CL ser derivado de uma linhagem mutada e possuir a característica de tolerância às imidazolinonas (imazethapyr + imazapic), sendo tolerante também ao grupo das sulfoniluréias (nicosulfuron), confirmando os resultados obtidos por Webster & Masson (2001). A fitotoxicidade observada no cultivar IRGA 417 demonstrou sua suscetibilidade a esses herbicidas, como foi relatado em estudos de deriva simulada na cultura do arroz (Bond et al, 2006;Kurtz & Street, 2003).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Esses resultados podem ser explicados pelo fato de o cultivar IRGA 422CL ser derivado de uma linhagem mutada e possuir a característica de tolerância às imidazolinonas (imazethapyr + imazapic), sendo tolerante também ao grupo das sulfoniluréias (nicosulfuron), confirmando os resultados obtidos por Webster & Masson (2001). A fitotoxicidade observada no cultivar IRGA 417 demonstrou sua suscetibilidade a esses herbicidas, como foi relatado em estudos de deriva simulada na cultura do arroz (Bond et al, 2006;Kurtz & Street, 2003).…”
Section: Resultsunclassified
“…O efeito do incremento da dose herbicida resultando em aumento na fitotoxicidade foi reportado em outros estudos, tanto para cultivares de arroz tolerantes como para cultivares sensíveis (Bond et al, 2006;Kurtz & Street, 2003;Levy Jr. et al, 2006;Ottis et al, 2003;Steele et al, 2002).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…This suggests that the slight depression for Mut1 and Mut6, and the continued decline in activity for control N12 in the untreated area may have been due to herbicide drift from the adjacent treated plots. Eberlein and Guttieri (1994) reported that amounts as small as 1/50th of the normal agricultural imazapyr rate reduced potato yields by two-thirds and Bond et al (2006) showed that a simulated drift rate of only 8 g a.i. ha -1 could reduce rice yield by 40%.…”
Section: Rs Rutherford Et Almentioning
confidence: 99%
“…Essa redução foi mais evidente para o herbicida imazethapyr + imazapic, que resultou em menor estatura de arroz-vermelho desde as menores doses estudadas, comparativamente ao nicosulfuron. O efeito de imazethapyr a partir de doses reduzidas também foi observado em estudos anteriores (Bond et al, 2006;Dal Magro, 2006). Da mesma forma que para a variável estatura, a massa seca da parte aérea sofreu redução com os tratamentos herbicidas, que foi mais evidente com o herbicida imazethapyr + imazapic, comparativamente ao nicosulfuron, exceto para as duas maiores doses (Figura 4).…”
Section: Figura 1 -unclassified